Costs are not necessarily correlated with threats in conservation landscapes. Issue 5 (8th July 2019) - Sacre, Edmond; Pressey, Robert L.; Bode, Michael
Abstract: The priority of an area for conservation is determined by three primary factors: its biodiversity value, the level of threat it is facing, and its cost. Although much attention has been paid to the spatial relationship between biodiversity value and threats, and between biodiversity value and costs, little is known about how costs and threats are spatially correlated. The orthodox assumption in conservation science is that costs and threats are positively correlated. Here, we adapt a classic economic theory of land use to explain how conservation scientists came to expect a positive correlation between costs and threats. We then use high‐resolution, ground‐truthed datasets of land sales and habitat clearance to show that this assumption is false in the state of Queensland, Australia. Our results provide an empirical counterargument to a widespread assumption in conservation science, and illustrate why spatial prioritization needs to include independent measures of costs and threats.